Breeding ecology of Rufous Potoo Nyctibius bracteatus in central Amazonian Brazil - Mello Barreiros, Marcelo Henrique; Tolentino, Mariana; Leite, Gabriel Augusto (Bulletin of the British Ornithologists' Club, 2022)
The smallest potoo, Rufous Potoo Nyctibius bracteatus is a little-known and inconspicuous species of the understorey in Amazonian terra firme forests, where it roosts by day. Currently, there are few published observations describing its natural history and reproductive ecology. We present data on nest and egg characteristics, nestling appearance, behaviour and development, and parental care, based on three different nests in three consecutive years at Reserva Florestal Adolpho Ducke, Manaus, central Amazonian Brazil. All nests had similar characteristics and the single egg at one nest was cream-coloured with brown spots. The young at one nest fledged when c.40 days old, but the other two nests were both predated by ant swarms, constituting the first report of such predation in the Nyctibiidae.